Placental Pathology and Placental Growth Factor (PlGF)/Vascular Endothelial Growth Factor Receptor-1 (VEGFR-1) Pathway Expression Evaluation in Fetal Congenital Heart Defects - Alexandru Cristian Bolunduț; Ximena Maria Mureșan; Rada Teodora Suflețel; Lavinia Patricia Mocan; Simina Pîrv; Sergiu Șușman; Carmen Mihaela Mihu (Life)
The heart and placenta have simultaneous embryologic development, the interactions between the two organs representing the heart–placental axis. They both share key developmental pathways, one of which involves the placental growth factor (PlGF) and its receptor, vascular endothelial growth factor receptor-1 (VEGFR-1). The aim of this study was to evaluate the placental pathology and the expression patterns of PlGF and VEGFR-1 in pregnancies with fetuses with congenital heart defects (CHDs). We analyzed placental gross and microscopic alterations between placentas from pregnancies with CHD fetuses and pregnancies with structurally normal heart fetuses. We also performed the immunohistochemical (IHC) assessment of the placental expression of PlGF and VEGFR-1 in the two groups. We discovered significant gross placental abnormalities in pregnancies with CHD fetuses, including a shorter umbilical cord, marginal or velamentous umbilical cord insertion, and a lower fetal-to-placental weight ratio. Also, 88.2% of the placentas in the CHD group displayed microscopic pathologic aspects. We demonstrated significant placental immunostaining for PlGF and VEGFR-1 in the syncytiotrophoblast and decidual cells compared to villous endothelial cells. We identified a lower placental IHC expression of PlGF in pregnancies with CHD fetuses compared to controls but no differences in the placental immunostaining pattern for VEGFR-1 between the two groups. Our study uncovered a potential role played by the PlGF/VEGFR-1 pathway in the development of CHDs through placental-mediated mechanisms.